Co-assembling system that exhibits bright circularly polarized luminescence. Issue 7 (7th February 2022) - Ryu, Naoya; Harada, Tomoyuki; Okazaki, Yutaka; Yoshida, Kyohei; Shirosaki, Tomohiro; Oda, Reiko; Kuwahara, Yutaka; Takafuji, Makoto; Ihara, Hirotaka; Nagaoka, Shoji
Abstract : A co-assembling system composed of a nonchiral metal-free dye and chiral-molecular-assembly template can be a promising candidate for circularly-polarized luminescent materials with both a high luminescence dissymmetry factor and strong emission. Abstract : We demonstrate that a co-assembling system comprising a nonchiral cyanine dye and an enantiomeric lysine-derived amphiphile assembly show circularly polarized luminescence with a high dissymmetry factor (| g lum | = 0.14) in combination with strong emission (quantum yield ϕ = 0.70, absorption coefficient ε = 3.7 × 10 5 M −1 cm −1 ). The circular polarization luminosity of the main transition band was calculated as 4.9 × 10 −2 .